Preclinical and Clinical Evidence of Lurbinectedin in Ovarian Cancer: Current Status and Future Perspectives - Musacchio, Lucia; Cicala, Carlo Maria; Salutari, Vanda; Camarda, Floriana; Carbone, Maria Vittoria; Ghizzoni, Viola; Giudice, Elena; Nero, Camilla; Perri, Maria Teresa; Ricci, Caterina; Tronconi, Francesca; Scambia, Giovanni; et al. (Frontiers in Oncology, 2022)
Lurbinectedin is an antitumor agent belonging to the natural marine-based tetrahydroisoquinoline family which has shown very promising clinical activity with a favorable safety profile in many types of cancer. Preclinical evidence showed that lurbinectedin inhibits active transcription and binds to GC-rich sequences, leading to irreversible degradation of RNA polymerase II, generation of single- and double-strand DNA breaks, and, as consequence, apoptosis of tumor cells. In addition, lurbinectedin has demonstrated modulation of tumor microenvironment and activity against cancer cells harboring homologous recombination DNA repair deficiency. Although considerable improvements have been made in the treatment of epithelial ovarian cancer, most patients with advanced disease experience recurrence with a dismal prognosis due to chemotherapy (mainly platinum) resistance. Platinum resistant/refractory ovarian cancer remains a difficult to treat setting of disease, and currently the exploration of new therapeutic approaches represents a main field of interest. Despite the CORAIL phase III study did not meet its primary endpoint, the results suggest that lurbinectedin might be a valid alternative for patients that have exhausted therapeutic options. This article will focus on the clinical evidence, the most recent investigations, and the future perspective regarding the use of lurbinectedin in ovarian cancer.